A convenient Way for the Etherification of p-Hydroxyacetophenone - Meng Guan, Tay; Zainab, Ngaini; Norazilawati, Muhamad Sarih; Siong Wan, Foo; Mee Hing, Tiong (Universiti Malaya, 2011)
Etherification is one of the important organic reactions especially in the drugs and liquid crystal compounds syntheses. This reaction was firstly reported by Williamson in 1850 for the etherification of aliphatic alcohol with alkyl halide (McMurry, 2004). However, etherification on phenolic compounds such as p-hydroxybenzaldehyde and p-hydroxyacetophenone is not as easy as those reported on aliphatic alcohols (Wright, 1997). The early example of etherification on p-hydroxybenzaldehyde was reported by Sugiyama ...